Child Rights Education for Participation and Development Primary Prevention - Desai, Murli (Rights-based Direct Practice with Children,, 2018)
The aims of child rights education are to make children and their primary duty-bearers aware of child rights so that they both can be empowered to together advocate for and apply them at their family, school and community levels. This sourcebook focuses on child rights education for primary prevention with reference to participation and development. The introductory chapter covers child rights values of peace, dignity, tolerance, freedom, equality and justice and child rights principles of dignity of the child, primary consideration to the best interests of the child, universality and non-discrimination, and state and societal accountability. Child rights to participation focuses on child rights for playing a decisive and responsible role in their own life and a participatory role in the family, schools, associations, community and with the state as citizens. Child rights to development includes child rights to free, compulsory, comprehensive and quality education, free of discrimination and violence; child rights to play, recreational, cultural, and artistic activities and media literacy; child rights to health with reference to physical health and hygiene, healthy and hygienic food and nutrition, sexual health and prevention of substance abuse; and child rights to environmental education with reference to child rights to environmental harmony and hygiene and child rights to sustainable environment. This is a must-read for researchers, trainers, and other professionals working on child rights issues across the world, and especially in developing countries. .